The Effect of Service Quality on Generation Z Customer Satisfaction at Janji Jiwa Outlets in Sorong City - Edwar, Rizka Cintya (Management Studies and Business journal, 2026)
The lifestyle trends of Generation Z, particularly their preference for spending time in cafés, have become an important factor for businesses seeking to enhance customer satisfaction. This study aims to analyze the effect of service quality on the satisfaction of Generation Z customers at Janji Jiwa cafés throughout Sorong City. The research employs a quantitative method with a sample size of 105 respondents. Data were collected using questionnaires with a Likert scale, and analyzed through simple linear regression using SPSS version 20. The results of this study indicate that service quality has a positive and significant effect on the satisfaction of Generation Z customers. This is because Generation Z often seeks comfortable cafés not only as a place to complete academic or professional tasks but also as a means of relaxation. The novelty of this study lies in its contribution to enriching the understanding of consumer satisfaction influenced by service quality, specifically within the context of Generation Z customers.